2020
DOI: 10.4102/sajr.v24i1.1875
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of pineapple juice as a negative oral contrast agent in magnetic resonance cholangiopancreatography

Abstract: Background: During magnetic resonance cholangiopancreatography (MRCP), the pancreatobiliary ducts can be obscured by the high-intensity signal from the stomach and duodenum. Pineapple juice may be an alternative to commercially available negative contrast agents, but has not been evaluated locally.Objectives: To evaluate the efficacy of a local, off-the-shelf pineapple juice preparation as a negative oral contrast agent for MRCP.Method: An observational, analytical study was conducted during January–December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, pineapple juice did not decrease the signal intensity in the stomach. 6 In our study, we observed that the group that received both ranitidine and hematinic syrup had decreased signal intensities in both duodenum and stomach. Govindarajan et al used date syrup as negative oral contrast and compared the image quality of pre- and post-oral contrast images of the same patients.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…However, pineapple juice did not decrease the signal intensity in the stomach. 6 In our study, we observed that the group that received both ranitidine and hematinic syrup had decreased signal intensities in both duodenum and stomach. Govindarajan et al used date syrup as negative oral contrast and compared the image quality of pre- and post-oral contrast images of the same patients.…”
Section: Discussionmentioning
confidence: 51%
“…Another reason could be that we relied more on 3D sequence to score the structure visualization score, as it is superior in depicting the individual parts of pancreaticobiliary ductal system, while two-dimensional sequences and MIP images were used for scoring the image quality in majority of the studies reported in literature. 2 5 6 7 12 13 14 15 16…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the proximity of the stomach and duodenum to the pancreatobiliary tree and the projectional nature of these images, 2D MRCP sequence has the potential technical limitation that the hyperintense intraluminal fluid signal within the adjacent stomach or duodenum may superimpose upon the pancreatobiliary tree, hindering comprehensive evaluation of this system (7)(8)(9)(10)(11). To overcome this drawback, some kinds of juice or syrup (including acai, blueberry, pineapple juice, and data syrup) has been proposed as the oral negative contrast agents to effectively decrease the high signal of the gastrointestinal tract (7,8,(12)(13)(14)(15) and improve MRCP image quality, but it is unfortunately not easy to get in such large volumes for clinical practice. Recently, it has been shown that oral administration of the effervescent agent can improve MRCP images, both qualitatively and quantitatively, for the purpose of biliary anatomy evaluation in the living liver donors (1).…”
Section: Introductionmentioning
confidence: 99%